REVIEW: THE IMPORTANCE OF MOLECULAR MARKERS IN PLANT BREEDING PROGRAMMES (Global Journal of Science Frontier Research, 2011)
Since the advent of restriction fragment length polymorphism (RFLP) markers, a range of other markers such as Random Amplified Polymorphism DNA (RAPD), amplified fragment length (AFLP), Simple sequence repeats (SSRS), etc has been introduced during the last two decades of the 20 th century to fulfill various demands of the last breeding programmes. Ever since their invention, they are being, constantly modified for enhanced utility as a means to solve problems and to bring about automation in the genome analysis, gene tagging, phylogenic analysis and selection of desirable genotypes. It is also evidence that molecular markers (non morphological markers) offer several advantages over the morphological markers (conventional phenotypic markers), as they provide data that can be analyzed objectively; giving new dimension to breeding especially with respect to the time required to developing new improved crop varieties. In terms of scientific progress, the old disciplines of quantitative genetics and plant taxonomy have been revived by the molecular marker approach, which have the immediate application in supportive research for advanced breeding programmes. Therefore, the success of DNA marker technology for bring genetic improvement in crop plants would depend on close interaction between plant breeders and biotechnologists, availability of skilled manpower and substantial financial investment on research.